2020
DOI: 10.1136/gutjnl-2020-320990
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in clinical practice: colorectal cancer chemoprevention in the average-risk population

Abstract: Colorectal cancer (CRC) is one of the most common and lethal malignancies in Western countries. Its development is a multistep process that spans more than 15 years, thereby providing an opportunity for prevention and early detection. The high incidence and mortality rates emphasise the need for prevention and screening. Many countries have therefore introduced CRC screening programmes. It is expected, and preliminary evidence in some countries suggests, that this screening effort will decrease CRC-related mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 98 publications
(205 reference statements)
4
52
0
Order By: Relevance
“…Evidence indicates that diets high in fiber and low in red and processed meats, as well as regular physical activity, have a protective effect on CRC development ( 99 ). Many studies confirmed that high dietary fiber intake is negatively correlated with CRC (RR=0.84) ( 100 ), especially fiber derived from grains and fruits ( 101 ).…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that diets high in fiber and low in red and processed meats, as well as regular physical activity, have a protective effect on CRC development ( 99 ). Many studies confirmed that high dietary fiber intake is negatively correlated with CRC (RR=0.84) ( 100 ), especially fiber derived from grains and fruits ( 101 ).…”
Section: Preventionmentioning
confidence: 99%
“…Although the impact of metformin use on CRC incidence in the general population is controversial, its role in reducing CRC incidence in patients with T2DM is positive. Moreover, consuming folic acid, magnesium, and dairy products reduces the risk of CRC, whereas the intake of tea, vitamin D, coffee, and omega-3 unsaturated fatty acids has controversial effects on CRC prevention ( 99 ).…”
Section: Preventionmentioning
confidence: 99%
“…The SELECT study compared the supplementation of selenium (as selenomethionine) and vitamin E in the incidence of prostate cancer. However, the study was interrupted before planned, because the data, contrary to the expectation, have not indicated potential beneficial effects of selenium or vitamin E. Despite the negative outcomes of SELECT (Dunn et al 2010 ; Klein et al 2011 ; Lippman et al 2009 ; Nicastro and Dunn 2013 ), the potential use of selenium in cancer prevention or treatment is still a matter of debate (Chapelle et al 2020 ; Vinceti et al 2018 ). Several experimental studies have indicated the potential anti-cancer properties of inorganic and organic forms of selenium (Álvarez-Pérez et al 2018 ; Gandin et al 2018 ; Gopalakrishna et al 2018 ; Krasowska et al 2019 ; Ruberte et al 2019 ; Sanmartín et al 2012 ; Sharma and Amin 2013 ; Spengler et al 2019 ; Steinbrenner et al 2013 ; Tan et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Medications that have not been as extensively studied, including difluoromethylornithine, erlotinib, and certain antioxidants, vitamins, and supplements, were excluded from this clinical practice update but have been covered in other recent reviews. 91,92…”
Section: Other Agentsmentioning
confidence: 99%